2004
DOI: 10.7863/jum.2004.23.5.715
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Appearance of Subcutaneous Angiolipomas

Abstract: Case ReportA 37-year-old man had multiple subcutaneous lumps on the torso and all extremities. These first became noticeable after puberty and had slowly increased in size and number over the years. They were variable in size, ranging from several millimeters to several centimeters. The lumps were firm, partially mobile, and smooth on palpation. The larger ones had a bosselated surface. Some were mildly tender on compression. Sonographic assessment of several of the larger lumps was requested before cosmetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…Although not frequent, internal vascularity was only seen in angiolipomas and not in superficial lipomas. The sonographic features of the angiolipomas in our study were similar to those found in previous studies 5 , 15 . The mixture of vessel structures with adipose tissue might also contribute to the heterogeneous echo texture, hyperechogenicity, and vascularity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although not frequent, internal vascularity was only seen in angiolipomas and not in superficial lipomas. The sonographic features of the angiolipomas in our study were similar to those found in previous studies 5 , 15 . The mixture of vessel structures with adipose tissue might also contribute to the heterogeneous echo texture, hyperechogenicity, and vascularity.…”
Section: Discussionsupporting
confidence: 89%
“…Angiolipomas are considered a variant of lipomas because they also have mature adipocytes with encapsulation. In addition to the features of lipomas, angiolipomas are also composed of a branching network of blood vessels, 7 , 14 specifically small‐caliber capillaries, and often contain fibrin thrombi with surrounding mature fat 6 , 15 . However, angiolipomas have a normal karyotype, unlike lipomas, which have karyotypic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonography is an attractive modality for evaluating superficial masses because of its availability, lack of radiation, lower cost, and higher resolution compared with magnetic resonance imaging. The sonographic appearance of superficial masses has been described by multiple authors, 2 , 4 – 6 and lipomas are known to have variable echogenicity ranging from hyperechoic to hypoechoic compared with skeletal muscle. The diagnostic accuracy of sonography in the evaluation of superficial masses remains controversial, with some authors reporting low diagnostic accuracy and urging caution 4 , 7 .…”
mentioning
confidence: 99%
“…Sie sind meist in der Handfläche vorzufinden und können aufgrund des weichen, indolenten Palpationsbefunds klinisch relativ einfach diagnostiziert werden. Daneben können auch andere mesenchymale Elemente (fibröse, chondroide, myxoide, Angiolipome) enthalten sein, was die sonografische Untersuchung erschweren kann (Choong 2004). Abb.…”
Section: Lipomeunclassified